Rancangan Pola Sistem Informasi Akuntansi Penerimaan dan Pengeluaran Kas: Studi Fenomenologi pada Situs Patirtaan Ngawonggo Tajinan Malang - Sekar Darma Revika; M. Sodik; Endah Puspitosarie (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
Accounting information system (AIS) is an important part of corporate financial management. This research aims to study the design pattern of AIS for cash receipts and disbursements using a phenomenological approach based on a background that illustrates how important AIS optimization is at the Ngawonggo Patirtaan Site. To investigate the experiences of four informants regarding the current AIS implementation, this study used qualitative phenomenology. Data were collected through observation, documentation, and in-depth interviews. Then, a model was used to analyze the relationship between theme attributes and meanings. The research was conducted at Ngawonggo Patirtaan Site, which is located in Tajinan District, Malang. The results showed that the current AIS at Ngawonggo Patirtaan Site is still simple but organized. Expenditures are allocated based on needs, but the cash receipt system uses a kotak asih. Periodic recording is done manually in the cash ledger. Information is provided through verbal reports every month. The absence of supporting facilities is a major obstacle. The results show that the AIS should be more integrated and organized. The design of the proposed AIS pattern includes online registration process, cash receipt through kotak asih, digital and manual recording of transactions, and periodic reports. It is expected that better use of AIS will improve the efficiency and accountability of financial management at Ngawonggo Patirtaan Site.